98 Barriers and opportunities in the integrated histopathological-molecular diagnosis of adult diffuse gliomas: a national survey of neuropathology units in UK&I - Vassili Crispi; Ute Pohl; Federico Roncaroli; Kathereena Kurian; Ashiward Merve; Peter Auguste; Arabella Scantlebury; Colin Watts; Victoria Wykes (Neuro-Oncology, 2026)
Abstract Introduction Integrated histopathological–molecular diagnosis is central to the contemporary classification and management of adult diffuse gliomas. The delivery of timely integrated diagnosis remains operationally complex, resource-intensive, and variably implemented across healthcare systems. Methods We conducted an online cross-sectional national survey of all 23 neuropathology units covering 34 adult neurosurgical units across the United Kingdom and Ireland to characterise current diagnostic pathways for adult diffuse gliomas. Results All centres deliver local immunohistochemistry. Only nine(39%) had comprehensive in-house molecular testing (e.g. next generation sequencing (NGS), Fluorescence In Situ Hybridisation (FISH), methylation array (MA)), seven in England alongside Glasgow and Dublin. Most centres(61%) used a mix of local and external molecular services, whereas eight centres outsourcing all molecular testing (five in England, two in Scotland, and one in Northern Ireland). Molecular diagnostics were delivered through parallel(65%) or sequential(17%) testing pathways, often requiring multiple assays per case for an integrated diagnosis. Time to final standard-of-care diagnosis was 15–21 days, but many centres reported exceeding 21 days, with molecular testing being the main cause of diagnostic delays. Significant barriers and opportunities: no single molecular assay is sufficient, current NGS does not provide results by the first MDT for decision-making(70%), whilst NGS is cheaper, it often lags behind DNA MA, complex molecular findings from NGS and MA need support from specialist scientists, technologies, IT systems, training and infrastructure are fragmented and limited across units, resulting in poor integration between systems and workflows. Conclusion Contemporary neuropathology pathways for adult diffuse gliomas are misaligned with the molecular complexity of modern classification systems. System-level redesign, incorporating integrated, tissue-efficient molecular diagnostics and coordinated service delivery models, is required to achieve timely, equitable, and sustainable integrated diagnosis.